Implementation of the quantitative Real-Time PCR for the molecular-genetic diagnostics of spinal muscular atrophy - Soloviov, O.O.; Livshits, G.B.; Podlesnaya, S.S.; Livshits, L.A. (Вiopolymers and Cell, 2010)
Aim. To develop an easy and reliable assay for quantitative analysis of the SMN1 gene exon 7 copy number with Real-Time PCR and a SYBR Green dye which can be used as a test-system for spinal muscular atrophy (SMA) diagnostics. Methods. For the quantification the SMN1 gene exon 7 copies we have used the approach, which is based on the comparison of ratio between PCR amplification of the genomic DNA sample and that of an internal standard (Albumin gene) for each subject tested. For the development and validation of the assay we tested the DNA samples from ten patients with SMA (homozygous deletion of the exon 7 in the SMN1 gene) which were previously analyzed using standard PCR-RFLP method and 42 control DNA samples from: 29 heterozygous carriers of the deletion of the exon 7 in the SMN1 gene, 13 individuals without SMN1 deletion, which were previously analyzed using linkage analysis of 2AE9.1 (D5S557) and LAS96 (D5S681) polymorphic microsatellite loci, and 10 samples from individuals of the general population. The results were calculated using standard Livak method (2–ΔΔCt method). Results. The mean ± SD of the 2–ΔΔCt ratios for the carriers of the heterozygous deletion of the exon 7 in the SMN1 gene is 0.475 ± 0.091; and for the controls – 0.909 ± 0.068. The results obtained don’t show overlapping between 2–Ct ratios at the carriers of the SMN1 heterozygous deletion and individuals without it (t =3.84, p > 0.05). Conclusions. This method can be used as a basis for creating the test-system for SMA DNA diagnostics, especially for the carrier screening.